China's financial crisis - the role of banks and monetary policy - Vo Phuong Mai Le; Kent Matthews; David Meenagh; Patrick Minford; Zhiguo Xiao (Cardiff University, Cardiff Business School, 2015)
This paper develops a model of the Chinese economy using a DSGE framework that accommodates a banking sector and money. The model is used to shed light on the period of the recent period of financial crisis. It differs from other applications in the use of indirect inference to estimate and test the fitted model. We find that the main shocks that hit China in the crisis were international and that domestic banking shocks were unimportant. Officially mandated bank lending and government spending were used to supplement monetary policy to aggressively offset shocks to demand. An analysis of the frequency of crises shows that crises occur on average about every half-century, with about a third accompanied by financial crises. We find that monetary policy can be used more vigorously to stabilise the economy, making direct banking controls and fiscal activism unnecessary.
Keywords: E3; E44; E52; C1; 330; DSGE model; Financial Frictions; China; Crises; Indirect Inference; Money; Credit